2016
DOI: 10.5005/jp-journals-10024-1818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silanization on Microtensile Bond Strength of Different Resin Cements to a Lithium Disilicate Glass Ceramic

Abstract: Applying one layer of a silane-coupling agent after etching the ceramic surface with hydrofluoric acid 10% enhanced the bond strength between resin cements and a glass ceramic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Other studies have shown that endocrowns are indicated in endodontically treated teeth and that they had a better fracture strength outcome when compared to conventional restorations 11,25 . However, Gré et al 30 reported similar value of fracture resistance with endocrowns and conventional crowns.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have shown that endocrowns are indicated in endodontically treated teeth and that they had a better fracture strength outcome when compared to conventional restorations 11,25 . However, Gré et al 30 reported similar value of fracture resistance with endocrowns and conventional crowns.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical success of a ceramic restoration depends on the quality and durability of the bond between ceramic and resin cement [24]. The protocol established for lithium disilicate-based ceramic cementation is the etching with HF and the application of a silane agent [25]. In the present study, various surface treatments were used, simplified or not, and the results showed that multiple surface treatments and adhesive protocols promoted significant changes in shear bond strength, disproving the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dental techniques and sciences are constantly evolving, resulting in an increasing number of material choices that can complicate clinical decisions. New questions are being raised following the rise of adhesive techniques [14][15][16][17][18][19][20][21], improvements in the mechanical properties of glass ceramics [22], and the introduction of hybrid ceramics to our profession.…”
Section: Introductionmentioning
confidence: 99%